Titanium oxide particles, titanium oxide particle dispersion, and method for producing titanium oxide particle dispersion
By adding manganese and/or cobalt components to the titanium oxide particles that are dissolved in tin components, the titanium oxide particle dispersion liquid is prepared, which solves the problems of photocatalytic activity inhibition and transparency maintenance in the resin material, and achieves long-term weather resistance and high Transparency.
Patent Information
- Application Number
- CN202080069606.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-02
- Filing Date
- 2020-09-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-09-29
AI Technical Summary
The prior art is difficult to suppress photocatalytic activity in resin materials for a long time, resulting in resin deterioration. At the same time, the excessive particle size of the inorganic ultraviolet absorber will reduce the transparency of the resin.
Manganese and/or cobalt components are added to the titanium oxide particles that have solid solution of tin components, and a titanium oxide particle dispersion is prepared through a mixing process to inhibit photocatalytic activity and control particle size to maintain the transparency of the resin.
Long-term weather resistance to resin materials is achieved, photocatalytic activity is suppressed, and the transparency and appearance design of the resin are maintained due to the small coloring.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to titanium oxide particles, a titanium oxide particle dispersion, and a method for producing the titanium oxide particle dispersion. Background Art
[0002] It is known that when resin molded products or films are exposed to ultraviolet rays contained in sunlight for a long period of time, mechanical properties such as elasticity and tensile strength are reduced, or cracks are generated, gloss is reduced, and appearance is deteriorated such as fading.
[0003] In order to solve these problems, organic ultraviolet absorbers such as benzotriazole compounds, triazine compounds and benzophenone compounds or inorganic ultraviolet absorbers such as titanium oxide and zinc oxide are sometimes added to the resin during molding and processing of the resin.
[0004] However, organic ultraviolet absorbers have a problem in that their ultraviolet absorption performance is gradually lost due to exposure to ultraviolet rays, and therefore are not suitable for applications requiring long-term weather resistance.
[0005] On the other hand, although the ultraviolet absorption performance of inorganic ultraviolet absorbers does not decrease even when exposed to ultraviolet rays, titanium oxide or zinc oxide generates active species that function as photocatalysts by absorbing ultraviolet rays, which in turn causes degradation of the resin in contact. Therefore, in order to obtain long-term weather resistance, it is necessary to suppress the influence of photocatalytic activity. In addition, if the particle size of titanium oxide or zinc oxide mixed in the resin is large, the transparency of the resin is reduced, so the particle size needs to be sufficiently small (Patent Document 1).
[0006] In order to avoid resin degradation caused by photocatalytic activity, it is generally known that, for example, a method of avoiding direct contact between titanium oxide and resin by covering the surface of titanium oxide particles with oxides or hydroxides such as aluminum, silicon, and zirconium; a method of reducing the photocatalytic activity of titanium oxide itself by dissolving dissimilar metals such as manganese or cobalt into the crystals of titanium oxide, etc. (Patent Document 2, Patent Document 3, Patent Document 4), etc.
[0007] However, the surface coating method using only the former is not sufficient to suppress the influence of photocatalytic activity for a long time; and in the latter method of solid solution of heterogeneous metals, although the photocatalytic activity can be fully suppressed to obtain long-term weather resistance, the coloring of titanium oxide caused by the solid solution of heterogeneous metals exists, thereby hindering the appearance design of the resin.
[0008] Prior art literature
[0009] Patent Literature
[0010] [Patent Document 1]: Japanese Patent Application Publication No. 2005-120137
[0011] [Patent Document 2]: Japanese Patent Application Publication No. 63-225532
[0012] [Patent Document 3]: Japanese Patent Application Publication No. 2003-327430
[0013] [Patent Document 4]: Japanese Patent Application Publication No. 2003-327431 Summary of the invention
[0014] Problem that the invention aims to solve
[0015] Therefore, an object of the present invention is to provide titanium oxide particles and a titanium oxide particle dispersion liquid. The titanium oxide particles are useful as an inorganic ultraviolet absorber that can impart long-term weather resistance to a resin material, sufficiently suppress photocatalytic activity, and have little coloration.
[0016] Solutions to the problem
[0017] In order to achieve the above-mentioned purpose, the inventors have repeatedly conducted in-depth studies and found that if manganese components and / or cobalt components are added to titanium oxide particles in which tin components are solid-dissolved, even if the manganese components / cobalt components are not solid-dissolved in titanium oxide, titanium oxide particles with sufficiently suppressed photocatalytic activity and less coloring can be obtained, thereby completing the present invention.
[0018] Therefore, the present invention provides titanium oxide particles, a member having the titanium oxide particles, a titanium oxide particle dispersion, and a method for producing the titanium oxide particle dispersion as shown below.
[0019] [1] A titanium oxide particle comprising: 1) a tin component, and 2) a manganese component and / or a cobalt component,
[0020] Here, only the tin component is dissolved in the titanium oxide particles, and the content of the manganese component and / or the cobalt component is 5 to 5000 in terms of the molar ratio of titanium to manganese and / or titanium to cobalt (Ti / Mn and / or Ti / Co).
[0021] [2] A member having a film of the titanium oxide particles described in [1].
[0022] [3] A titanium oxide particle dispersion comprising: 1) titanium oxide particles in which a tin component is solid-dissolved, and 2) a manganese component and / or a cobalt component,
[0023] The content of the manganese component and / or the cobalt component is 5 to 5000 respectively in terms of the molar ratio of titanium to manganese and / or titanium to cobalt (Ti / Mn and / or Ti / Co).
[0024] [4] The titanium oxide particle dispersion according to [3], wherein
[0025] The color difference (ΔE*) between (a) a titanium oxide particle dispersion having a solid solution of tin and a molar ratio of titanium to tin (Ti / Sn) of 20 at a solid content concentration of 1 mass % and (b) the titanium oxide particle dispersion according to claim 3 ab ) is below 30.
[0026] [5] The titanium oxide particle dispersion according to [3] or [4],
[0027] It also contains silicon.
[0028] [6] The titanium oxide particle dispersion according to any one of [3] to [5],
[0029] The content of the tin component dissolved in titanium oxide is 1 to 1000 in terms of the molar ratio of titanium to tin (Ti / Sn).
[0030] [7] The titanium oxide particle dispersion according to any one of [3] to [6],
[0031] The content of the manganese component and / or the cobalt component is 10 to 3000 in terms of the molar ratio of titanium to manganese and / or titanium to cobalt (Ti / Mn and / or Ti / Co).
[0032] [8] The method for producing a titanium oxide particle dispersion according to [3] to [7], characterized in that it comprises the following steps (1) to (4):
[0033] (1) a step of preparing a peroxotitanic acid solution containing a tin component from a raw material titanium compound, a tin compound, an alkaline substance, hydrogen peroxide and an aqueous dispersion medium;
[0034] (2) a step of heating the peroxotitanic acid solution containing tin component produced in the above step (1) at 80 to 250° C. under pressure control to obtain a titanium oxide particle dispersion containing tin component;
[0035] (3) a step of obtaining an aqueous solution or aqueous dispersion of a manganese component and / or a cobalt component from a raw material manganese compound and / or a raw material cobalt compound and an aqueous dispersion medium;
[0036] (4) A step of mixing the titanium oxide particle dispersion containing the tin component produced in the step (2) and the aqueous solution or aqueous dispersion of the manganese component and / or the cobalt component produced in the step (3).
[0037] Effects of the Invention
[0038] The titanium oxide particles of the present invention, especially the titanium oxide particle dispersion, have their photocatalytic activity greatly suppressed, so even if they are mixed with a resin or coated on the surface of a resin, they can avoid degradation caused by the photocatalytic activity. In addition, since they are less colored and thus have high transparency, they do not hinder the appearance design of the resin. Therefore, the titanium oxide particles of the present invention and their dispersion can be used as an inorganic ultraviolet absorber mixed with a resin for outdoor use or coated on the surface of a resin. DETAILED DESCRIPTION
[0039] Hereinafter, the present invention will be described in detail.
[0040] <Titanium Oxide Particles>
[0041] The titanium oxide particles of the present invention are titanium oxide particles containing: 1) a tin component, and 2) a manganese component and / or a cobalt component. Among them, only the tin component is solid-dissolved in the titanium oxide particles, and the content of the manganese component and / or the cobalt component is 5 to 5000 in terms of the molar ratio of titanium to manganese and / or titanium to cobalt (Ti / Mn and / or Ti / Co), respectively, and it is particularly preferred to use it as a dispersion liquid.
[0042] <Titanium Oxide Particle Dispersion>
[0043] The titanium oxide particle dispersion of the present invention contains 1) titanium oxide particles in which a tin component is solid-dissolved, and 2) a manganese component and / or a cobalt component in an aqueous dispersion medium.
[0044] Here, in this specification, the solid solution refers to a phase in which atoms located at the lattice points of a certain crystal phase are replaced by other atoms, or other atoms are embedded in the lattice gaps, that is, a phase that is considered to be a mixed phase in which other substances are dissolved in a certain crystal phase, and the crystal phase is a homogeneous phase. The substitutional solid solution in which the solvent atoms located at the lattice points are replaced by the solute atoms is called a substitutional solid solution, and the solute atoms are inserted into the lattice gaps is called an intrusive solid solution, and in this specification, they are all regarded as solid solutions.
[0045] The titanium oxide particles of the present invention are characterized in that the titanium oxide particles form a solid solution with tin atoms. The solid solution may be a substitutional type or an intrusive type. The substitutional solid solution of titanium oxide is a substitutional solid solution formed by the titanium site of the titanium oxide crystal being replaced by various metal atoms; the intrusive solid solution of titanium oxide is an intrusive solid solution formed by the entry of various metal atoms into the lattice gap of the titanium oxide crystal. If various metal atoms are dissolved in titanium oxide, when the crystal phase is measured by X-ray diffraction or the like, only the peak of the crystal phase of titanium oxide is observed, and the peaks of the compounds of the various metal atoms added are not observed.
[0046] There is no particular limitation on the method of dissolving a dissimilar metal in a metal oxide crystal, and examples thereof include a gas phase method (CVD method, PVD method, etc.), a liquid phase method (hydrothermal method, sol / gel method, etc.), and a solid phase method (high temperature sintering method, etc.).
[0047] As the crystal phase of titanium oxide particles, three types of rutile, anatase and brookite are generally known, and the titanium oxide particles are preferably mainly anatase or rutile. It should be noted that the "mainly" mentioned here means that in the whole titanium oxide particles, 50% by mass or more of the titanium oxide particles of the crystal phase are contained, preferably 70% by mass or more, more preferably 90% by mass or more, and 100% by mass may be contained.
[0048] In addition, the dispersion medium of the dispersion liquid generally uses an aqueous solvent, preferably water, and a mixed solvent of a hydrophilic organic solvent and water that can be mixed with water in any proportion can also be used. As water, it is preferably purified water such as filtered water, deionized water, distilled water and pure water. In addition, as a hydrophilic organic solvent, it is preferably alcohols such as methanol, ethanol and isopropanol; glycols such as ethylene glycol; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and propylene glycol n-propyl ether. When a mixed solvent is used, the proportion of the hydrophilic organic solvent in the mixed solvent is more than 0% by mass, preferably less than 50% by mass, more preferably less than 20% by mass, and further preferably less than 10% by mass.
[0049] The titanium oxide particles are titanium oxide particles in which tin components are solid-dissolved in titanium oxide used as an ultraviolet absorber, preferably titanium oxide particles in which tin components are solid-dissolved, but manganese components and cobalt components are not solid-dissolved. This is because if manganese components and cobalt components are solid-dissolved, titanium oxide is colored, which may hinder the appearance design of the applicable resin. It should be noted that the titanium oxide particle dispersion of the present invention "containing manganese components and / or cobalt components" means that the manganese components and / or cobalt components are contained in the dispersion, but the form in which manganese components and / or cobalt components are solid-dissolved in the titanium oxide particles is not included.
[0050] The tin component dissolved in the titanium oxide particles is a component for suppressing the photocatalytic activity, and any component derived from a tin compound may be used, for example, a metal element of tin (Sn), tin oxides (SnO, SnO 2 ), tin hydroxide, tin chloride (SnCl 2 SnCl 4 ), tin nitrate (Sn(NO 3 ) 2 ), tin sulfate (SnSO 4 ), tin halides (Br, I), tin oxyacid salts (Na 2 SnO3 , K 2 SnO 3 ), tin complexes, etc., and one or more of them can also be used in combination. Among them, it is preferred to use tin oxides (SnO, SnO 2 ), tin chloride (SnCl 2 SnCl 4 ), tin sulfate (SnSO 4 ), tin oxygen salts (Na 2 SnO 3 , K 2 SnO 3 ).
[0051] The content of the tin component in the titanium oxide particles is preferably 1 to 1000, more preferably 5 to 500, and further preferably 5 to 100 in terms of the molar ratio of titanium to tin (Ti / Sn). This is because when the molar ratio is less than 1, the content of titanium oxide is reduced, which sometimes results in the inability to fully exert the ultraviolet absorption effect; when the molar ratio exceeds 1000, the inhibitory effect of the photocatalytic activity sometimes becomes insufficient. It should be noted that the component dissolved in titanium oxide is preferably only tin.
[0052] As the manganese component and / or cobalt component added to the titanium oxide particles, there can be listed metals of manganese and / or cobalt, oxides of manganese and / or cobalt, hydroxides of manganese and / or cobalt, chlorides of manganese and / or cobalt, nitrates of manganese and / or cobalt, sulfates of manganese and / or cobalt, halides (Br, I) of manganese and / or cobalt, oxyacid salts of manganese and / or cobalt, complexes of manganese and / or cobalt, etc. One or more of these can be used.
[0053] The content of the manganese component and / or the cobalt component added to the titanium oxide particles can be appropriately selected according to the type of the metal component, and is 5 to 5000 in terms of the molar ratio of titanium to manganese and / or titanium to cobalt (Ti / Mn and / or Ti / Co), respectively.
[0054] When manganese is selected as the metal component added to the titanium oxide particles, the manganese component may be any component derived from a manganese compound, for example, manganese metal element (Mn), manganese oxide (MnO, MnO 2 , Mn 2 O 3 , Mn 3 O 4 ), manganese hydroxide, manganese chloride (MnCl 2 ), manganese nitrate (Mn(NO 3 ) 2 ), manganese sulfate (MnSO 4), manganese halides (Br, I), manganese acid and manganese oxyacid salts (H 2 MnO 4 、HMnO 4 、Na 2 MnO 4 、 2 MnO 4 , K 2 MnO 4 、KMnO 4 ), manganese complexes, etc., or one or more of them may be combined. Among them, manganese chloride (MnCl 2 ), manganese nitrate (Mn(NO 3 ) 2 ), manganese sulfate (MnSO 4 ).
[0055] The amount of manganese added to the titanium oxide particles is preferably 5 to 5000, more preferably 10 to 3000, and even more preferably 10 to 1000 in terms of the molar ratio of titanium to manganese (Ti / Mn). This is because when the molar ratio is less than 5, the content of titanium oxide is reduced, and the ultraviolet absorption effect may not be fully exerted; when the molar ratio exceeds 5000, the photocatalytic activity suppression effect may become insufficient.
[0056] When cobalt is selected as the metal component added to the titanium oxide particles, the cobalt component may be any component derived from a cobalt compound, for example, cobalt metal element (Co), cobalt oxide (CoO, Co 2 O 3 ), cobalt hydroxide, cobalt chloride (CoCl 2 ), cobalt nitrate (Co(NO 3 ) 2 ), cobalt sulfate (CoSO 4 ), cobalt halides (Br, I), cobalt acids and cobalt oxyacids, cobalt complexes, etc., and one or more of them may be combined. Among them, cobalt chloride (CoCl 2 ), cobalt nitrate (Co(NO 3 ) 2 ), cobalt sulfate (CoSO 4 ).
[0057] The amount of the cobalt component added to the titanium oxide particles is preferably 5 to 5000, more preferably 10 to 3000, and further preferably 10 to 1000 in terms of the molar ratio of titanium to cobalt (Ti / Co). The reason for this is that when the molar ratio is less than 5, the content of titanium oxide is reduced, and the ultraviolet absorption effect may not be fully exerted; when the molar ratio exceeds 5000, the photocatalytic activity inhibition effect may become insufficient.
[0058] When manganese and cobalt are selected as metal components added to the titanium oxide particles, the amount of each component is within the above range, but the molar ratio of titanium to the total amount of each component [Ti / (Mn+Co)] is 5 or more and less than 10,000.
[0059] The titanium oxide particles may be used alone or in combination of two or more.
[0060] The titanium oxide particle dispersion may further contain a silicon component. When the silicon component is added, aggregation of the titanium oxide particles that occurs when the manganese component and / or the cobalt component is added can be suppressed.
[0061] The silicon component may be any component derived from a silicon compound, and examples thereof include silicon metal element (Si), silicon oxide (SiO, SiO 2 ), silicon alkoxide (Si(OCH 3 ) 4 、 Si(OC 2 H 5 ) 4 、Si(OCH(CH 3 ) 2 ) 4 ), silicates (sodium salts, potassium salts), and active silicic acid obtained by removing sodium or potassium ions from the silicates, etc., and one or more of them can be used in combination. Among them, silicates (sodium silicate) or active silicic acid are preferably used.
[0062] The silicon component may be mixed with a solution or dispersion of a manganese component and / or a cobalt component before being mixed into the titanium oxide particle dispersion; or the silicon component may be mixed into the titanium oxide particle dispersion in advance and then the solution or dispersion of the manganese component and / or the cobalt component may be mixed.
[0063] The content of the silicon component in the titanium oxide particle dispersion is preferably 0.1 to 1000, more preferably 0.5 to 200, and further preferably 1 to 100 in terms of the molar ratio of titanium to silicon (Ti / Si). This is because, when the molar ratio is less than 0.1, the content of titanium oxide is reduced, and the ultraviolet absorption effect may not be fully exerted; and when the molar ratio exceeds 1000, the effect of suppressing aggregation may become insufficient.
[0064] After adjusting the solid content concentration of the titanium oxide particle dispersion to 1 mass %, a transmission measurement was performed using a colorimeter with distilled water as a reference (according to JIS Z8722 (field of view: 10 degrees, light source: D65, measurement conditions: St, f, W10)), and the chromaticity value (L*a*b*) of the titanium oxide particle dispersion was obtained.
[0065] The degree of coloration of the titanium oxide particle dispersion of the present invention is determined by the color difference (ΔE* ab ) for evaluation.
[0066] (a) Comparative sample: a titanium oxide particle dispersion (solid content concentration 1 mass %) in which a tin component is solid-dissolved and the content of the tin component is 20 in terms of the molar ratio of titanium to tin (Ti / Sn)
[0067] (b) Evaluation object sample: a titanium oxide particle dispersion of the present invention, i.e., a titanium oxide particle dispersion containing 1) titanium oxide particles in which a tin component is solid-dissolved, and 2) titanium oxide particles in which a manganese component and / or a cobalt component is contained, wherein the content of the manganese component and / or the cobalt component is 5 to 5000 in terms of a molar ratio of titanium to manganese and / or titanium to cobalt (Ti / Mn and / or Ti / Co) (solid content concentration 1 mass %).
[0068] Specifically, after adjusting the dispersion of each of the comparative sample and the sample to be evaluated to a solid content concentration of 1 mass %, the color difference (Δ E*) between the two chromaticity values (L*a*b*) obtained by the above method was calculated according to the following calculation formula described in JIS Z8781-4. ab ).
[0069] [Calculation formula 1]
[0070]
[0071] The titanium oxide particle dispersion in which the tin component as a comparative sample was solid-dissolved so that the molar ratio of titanium to tin (Ti / Sn) was 20 was less colored and did not impair the design properties of the resin even when blended into the resin or applied on the surface.
[0072] Color difference with comparison sample (ΔE* ab ) is preferably 30 or less, more preferably 20 or less.
[0073] This is because when the color difference exceeds 30, the appearance design of the resin may be impaired due to coloring.
[0074] As an apparatus for measuring the chromaticity value (L*a*b*) of the dispersion, for example, a spectrophotometric colorimeter and turbidity simultaneous measuring instrument TZ7700 (manufactured by Nippon Denshoku Industries Co., Ltd.) and a spectrophotometer and colorimeter CM-5 (manufactured by Konica Minolta Japan Co., Ltd.) can be used.
[0075] The volume-based 50% cumulative distribution diameter (hereinafter sometimes referred to as D) of the titanium oxide particles in the titanium oxide particle dispersion to which the manganese component and / or the cobalt component is added is measured by a dynamic light scattering method using laser. 50 ) is preferably 3 to 50 nm, more preferably 3 to 30 nm, and more preferably 3 to 20 nm. The reason is that in the above D 50 When the wavelength is less than 3 nm, the ultraviolet absorption effect may be insufficient. 50 When the particle size exceeds 50 nm, the dispersion may become opaque.
[0076] The 90% cumulative distribution diameter (hereinafter sometimes referred to as D) on a volume basis was measured by a dynamic light scattering method using laser. 90 ) is preferably 5 to 100 nm, more preferably 5 to 80 nm. The reason is that in the above D 90 When the wavelength is less than 5 nm, the ultraviolet absorption effect may be insufficient. 90 When the particle size exceeds 100 nm, the dispersion may become opaque.
[0077] The titanium oxide particles of the present invention are D 50 and D 90 When the amount of fine particles is within the above range, it has an ultraviolet absorption effect and the dispersion liquid is transparent, which is preferred.
[0078] It should be noted that the D of the titanium oxide particles in the above dispersion is measured as 50 and D 90 As the device, for example, ELSZ-2000ZS (manufactured by Otsuka Electronics Co., Ltd.), Nano Track UPA-EX150 (manufactured by Nikkiso Co., Ltd.), LA-910 (manufactured by Horiba, Ltd.), etc. can be used.
[0079] <Method for producing titanium oxide particle dispersion>
[0080] The titanium oxide particle dispersion of the present invention is prepared by separately preparing a titanium oxide particle dispersion containing a tin component in a solid solution and an aqueous solution or dispersion of a manganese component and / or a cobalt component, and mixing the titanium oxide particle dispersion containing a tin component in a solid solution and the solution or dispersion of the manganese component and / or a cobalt component.
[0081] Specific examples of the method for producing a titanium oxide particle dispersion containing a manganese component and / or a cobalt component and in which a tin component is solid-dissolved include a method having the following steps (1) to (4).
[0082] (1) A process for preparing a peroxotitanic acid solution containing a tin component from a raw material titanium compound, a tin compound, an alkaline substance, hydrogen peroxide and an aqueous dispersion medium;
[0083] (2) a step of heating the peroxotitanic acid solution containing tin component produced in the above step (1) at 80 to 250° C. under pressure control to obtain a titanium oxide particle dispersion containing tin component;
[0084] (3) a step of producing an aqueous solution or aqueous dispersion of a manganese component and / or a cobalt component from a raw material manganese compound and / or a raw material cobalt compound and an aqueous dispersion medium;
[0085] (4) A step of mixing the titanium oxide particle dispersion containing the tin component produced in the step (2) and the aqueous solution or aqueous dispersion of the manganese component and / or the cobalt component produced in the step (3).
[0086] Steps (1) to (2) are steps for obtaining a dispersion of titanium oxide particles containing a solid solution of tin; step (3) is a step for obtaining an aqueous solution or a water dispersion of a manganese component and / or a cobalt component; and step (4) is a step for finally obtaining a dispersion containing titanium oxide particles containing a solid solution of tin and a manganese component and / or a cobalt component.
[0087] Under the following premise, each process is described in detail.
[0088] Process (1):
[0089] In step (1), a raw material titanium compound, a tin compound, an alkaline substance, and hydrogen peroxide are reacted in an aqueous dispersion medium to produce a peroxotitanic acid solution containing a tin component.
[0090] As the reaction method, any of the following methods i) to iii) may be used.
[0091] i) A method in which a tin compound is added to and dissolved in a raw material titanium compound and an alkaline substance in an aqueous dispersion medium to form titanium hydroxide containing a tin component, impurity ions other than metal ions contained therein are removed, and hydrogen peroxide is added to form peroxytitanic acid containing a tin component;
[0092] ii) A method of adding an alkaline substance to a raw material titanium compound in an aqueous dispersion medium to form titanium hydroxide, and after removing impurity ions other than metal ions contained therein, adding a tin compound, and then adding hydrogen peroxide to form peroxytitanic acid containing a tin component;
[0093] iii) A method of adding an alkaline substance to a raw titanium compound in an aqueous dispersion medium to form titanium hydroxide, removing impurity ions other than metal ions contained therein, adding hydrogen peroxide to form peroxytitanic acid, and then adding a tin compound to form peroxytitanic acid containing a tin component.
[0094] It should be noted that, in the previous stage of the method i), the “raw material titanium compound and alkaline substance in the aqueous dispersion medium” may be divided into two aqueous dispersion media in the form of “aqueous dispersion medium in which the raw material titanium compound is dispersed” and “aqueous dispersion medium in which the alkaline substance is dispersed”, and the two solutions may be mixed after the tin compound is dissolved in one or both solutions, depending on the solubility of the tin compound in the two solutions.
[0095] After the peroxotitanic acid containing the tin component is obtained in this way, it is subjected to a hydrothermal reaction in the step (2) described later, thereby obtaining titanium oxide particles in which the tin component is solid-dissolved in titanium oxide.
[0096] Here, as the raw material titanium compound, for example, inorganic acid salts such as titanium chloride, titanium nitrate and titanium sulfate; organic acid salts such as titanium formic acid, titanium citric acid, titanium oxalic acid, titanium lactic acid and titanium glycolic acid; titanium hydroxide precipitated by adding alkali to these aqueous solutions and hydrolyzing them; one or more of them can also be used in combination. Among them, titanium chloride (TiCl 3 、TiCl 4 ).
[0097] As the tin compound and the aqueous dispersion medium, the above substances are used in the above-mentioned combination manner. It should be noted that the concentration of the raw material titanium compound aqueous solution formed by the raw material titanium compound and the aqueous dispersion medium is 60 mass % or less, particularly preferably 30 mass % or less. The lower limit of the concentration can be appropriately selected, and is usually preferably 1 mass % or more.
[0098] The alkaline substance is a substance that smoothly converts the raw titanium compound into titanium hydroxide, and examples thereof include hydroxides of alkali metals or alkaline earth metals such as sodium hydroxide and potassium hydroxide; and amine compounds such as ammonia, alkanolamines, and alkylamines. Among them, ammonia is particularly preferably used, and is added in an amount such that the pH of the aqueous solution of the raw titanium compound is 7 or more, and particularly 7 to 10. It should be noted that the alkaline substance can also be used in the form of an aqueous solution of appropriate concentration together with the above-mentioned aqueous dispersion medium.
[0099] Hydrogen peroxide is used to convert the above-mentioned raw titanium compound or titanium hydroxide into peroxytitanic acid, that is, into a titanium oxide compound containing a Ti-OO-Ti bond, and is usually used in the form of hydrogen peroxide. The amount of hydrogen peroxide added is preferably 1.5 to 20 times the molar amount of the total amount of Ti and Sn. In addition, in the reaction of adding hydrogen peroxide to convert the raw titanium compound or titanium hydroxide into peroxytitanic acid, the reaction temperature is preferably 5 to 80°C, and the reaction time is preferably 30 minutes to 24 hours.
[0100] The peroxotitanic acid solution containing tin component obtained in this way may also contain alkaline substances or acidic substances for pH adjustment. As the alkaline substances mentioned here, for example, ammonia, sodium hydroxide, calcium hydroxide, alkylamines, etc. may be cited. As acidic substances, for example, inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, carbonic acid, phosphoric acid, hydrogen peroxide, and organic acids such as formic acid, citric acid, oxalic acid, lactic acid, and glycolic acid may be cited. In this case, from the viewpoint of the safety of the treatment, the pH value of the peroxotitanic acid solution containing tin component obtained is preferably 1 to 9, particularly preferably 4 to 7.
[0101] Process (2):
[0102] In step (2), the peroxotitanic acid solution containing tin component obtained in the above step (1) is subjected to a hydrothermal reaction for 0.01 to 24 hours under pressure control at a temperature of 80 to 250° C., preferably 100 to 250° C. From the viewpoint of reaction efficiency and controllability of the reaction, the appropriate reaction temperature is 80 to 250° C., and as a result, the peroxotitanic acid containing tin component is converted into titanium oxide particles. It should be noted that the "under pressure control" mentioned here means that when the reaction temperature exceeds the boiling point of the dispersion medium, the reaction temperature is maintained by appropriately pressurizing in a form that can maintain the reaction temperature, and also includes the case where the temperature is controlled to atmospheric pressure when the temperature is below the boiling point of the dispersion medium. The pressure used here is generally about 0.12 to 4.5 MPa, preferably about 0.15 to 4.5 MPa, and more preferably about 0.20 to 4.5 MPa. The reaction time is preferably 1 minute to 24 hours. Through this step (2), a titanium oxide particle dispersion containing tin component as titanium oxide particles is obtained.
[0103] The particle size of the titanium oxide particles obtained here is preferably within the above range, and the particle size can be controlled by adjusting the reaction conditions. For example, the particle size can be reduced by shortening the reaction time and the heating time.
[0104] Process (3):
[0105] In step (3), unlike steps (1) to (2), a raw material manganese compound and / or raw material cobalt compound is dissolved or dispersed in an aqueous dispersion medium to produce an aqueous solution or dispersion of a manganese component and / or a cobalt component.
[0106] As the raw material manganese compound, the above-mentioned manganese compounds can be cited, for example, manganese metal element (Mn), manganese oxide (MnO, MnO 2 , Mn 2 O 3 , Mn 3 O 4 ), manganese hydroxide, manganese chloride (MnCl 2 ), manganese nitrate (Mn(NO 3 ) 2 ), manganese sulfate (MnSO 4 ), manganese halides (Br, I), manganese acid and manganese oxyacid salts (H 2 MnO 4 、HMnO 4 、Na 2 MnO 4 、Na 2 MnO 4 , K 2 MnO 4 、KMnO 4 ), manganese complexes, etc. One or more of them may be combined. Among them, manganese chloride (MnCl 2 ), manganese nitrate (Mn(NO 3 ) 2 ), manganese sulfate (MnSO 4 ).
[0107] Examples of the raw material cobalt compound include the above-mentioned cobalt compounds, for example, cobalt metal element (Co), cobalt oxide (CoO, Co 2 O 3 ), cobalt hydroxide, cobalt chloride (CoCl 2 ), cobalt nitrate (Co(NO 3 ) 2 ), cobalt sulfate (CoSO 4 ), cobalt halides (Br, I), cobalt acid and cobalt oxyacids, cobalt complexes, etc. One or more of them may be combined. Among them, cobalt chloride (CoCl 2 ), cobalt nitrate (Co(NO 3 ) 2 ), cobalt sulfate (CoSO 4 ).
[0108] The concentration of the raw material manganese compound in the aqueous solution or aqueous dispersion of the manganese component and / or cobalt component produced in step (3) is preferably 0.001 to 10% by mass, more preferably 0.01 to 5% by mass. The concentration of the raw material cobalt compound is preferably 0.001 to 10% by mass, more preferably 0.01 to 5% by mass.
[0109] Furthermore, the aqueous solution or aqueous dispersion of the manganese component and / or the cobalt component may contain a silicon compound dissolved or dispersed therein.
[0110] Examples of silicon compounds include silicon metal (Si), silicon oxides (SiO, SiO 2 ), silicon alkoxide (Si(OCH 3 ) 4 、Si(OC 2 H 5 ) 4 、Si(OCH(CH 3 ) 2 ) 4 ), silicates (sodium salts, potassium salts), and active silicic acid obtained by removing sodium or potassium ions from the silicates, etc., and one or more of them may be combined. Among them, silicates (sodium silicate) or active silicic acid are preferred. Active silicic acid is obtained by, for example, adding a cation exchange resin to a sodium silicate aqueous solution obtained by dissolving sodium silicate in pure water and removing sodium ions. It is preferred to add the cation exchange resin in such a way that the pH of the obtained active silicic acid solution is 2 to 10, preferably 2 to 5.
[0111] When the silicon compound is dissolved or dispersed in the aqueous solution or aqueous dispersion of the manganese component and / or the cobalt component produced in step (3), it is preferred to use SiO 2 The silicon compound is dissolved or dispersed so as to be 0.001 to 10% by mass, preferably 0.01 to 5% by mass.
[0112] The solution or dispersion of the manganese component and / or cobalt component thus obtained may contain an alkaline substance or an acidic substance for the purpose of adjusting the pH, etc. The alkaline substance and the acidic substance mentioned here may be the same as those in the above step (1), and the pH adjustment may be carried out in the same manner as above.
[0113] Process (4):
[0114] In step (4), the titanium oxide particle dispersion obtained in step (2) and the aqueous solution or aqueous dispersion of the manganese component and / or the cobalt component obtained in step (3) are mixed. There is no particular limitation on the mixing method, and it can be a method of stirring with a stirrer or a method of dispersing with an ultrasonic disperser. The temperature during mixing is preferably 20 to 100° C., and the mixing time is preferably 1 minute to 3 hours. Regarding the mixing ratio, the mixing can be performed in such a way that the molar ratio of Ti and Mn and / or Co in each titanium oxide particle dispersion becomes the molar ratio as described above.
[0115] The titanium oxide particle dispersion obtained in the above steps (1) to (4) may contain an alkaline substance or an acidic substance for adjusting pH, etc., and the above substances may be used as pH adjusters. In addition, ion exchange treatment or filtration and washing treatment may be performed to adjust the concentration of ion components, or solvent replacement treatment may be performed to change the solvent components.
[0116] The mass of titanium oxide particles contained in the titanium oxide particle dispersion can be calculated from the mass and concentration of the titanium oxide particle dispersion. It should be noted that the concentration of the titanium oxide particle dispersion can be determined by sampling a portion of the titanium oxide particle dispersion, heating at 105° C. for 1 hour to volatilize the solvent, and calculating the mass of the non-volatile component (titanium oxide particles) and the mass of the sampled titanium oxide particle dispersion according to the following formula.
[0117] Concentration of titanium oxide particle dispersion (%) = [mass of non-volatile component (g) / mass of titanium oxide particle dispersion (g)] × 100
[0118] The total concentration of the manganese component and / or cobalt component and the titanium oxide particles in the titanium oxide particle dispersion prepared in this way is preferably 0.1 to 50% by mass, and particularly preferably 0.5 to 30% by mass, from the perspective of ease of blending with the resin and coating on the surface. Regarding concentration adjustment, when the concentration is higher than the desired concentration, the concentration can be reduced by adding an aqueous solvent for dilution; when the concentration is lower than the desired concentration, the concentration can be increased by volatilizing or filtering the aqueous solvent. It should be noted that the concentration can be calculated in the above manner.
[0119] The dispersion obtained in the above manner can be used to form a coating having a desired thickness, preferably 10 nm to 10 μm, on a substrate (resin molded article) by a known coating method (brush coating, spraying, dipping, roll coater, etc.), and can be dried or heated as needed.
[0120] The member of the present invention is a member having the titanium oxide particle film of the present invention, and is a member having a film formed using the titanium oxide particle dispersion of the present invention inside or on the surface of a substrate (resin molded article) as described above.
[0121] [Example]
[0122] The present invention is specifically described below with reference to the following examples and comparative examples, but the present invention is not limited to the following examples. Various measurements in the present invention are performed as follows. (1) The 50% cumulative distribution diameter and the 90% cumulative distribution diameter (D 50 and D 90 )
[0123] D of titanium oxide particles in the dispersion 50 and D 90 The particle size distribution was calculated as a 50% cumulative distribution diameter and a 90% cumulative distribution diameter based on volume measured by a dynamic light scattering method using laser light using a particle size distribution measuring apparatus (ELSZ-2000ZS (manufactured by Otsuka Electronics Co., Ltd., Japan).
[0124] (2) Color difference (ΔE*) of titanium oxide particle dispersion ab )
[0125] The color difference of the titanium oxide particle dispersion was calculated based on the color values of the titanium oxide particle dispersion to be evaluated and the comparative sample measured with a colorimeter.
[0126] As a comparative sample, a titanium oxide particle dispersion (Preparation Example 1-1 described below) was used in which a tin component was solid-solved so that the molar ratio (Ti / Sn) of the titanium component to the tin component was 20 without adding a manganese component and a cobalt component.
[0127] Specifically, the chromaticity value (L*a*b*) is obtained by adjusting the solid content concentration of the titanium oxide particle dispersion to be measured to 1 mass %, and then performing transmission measurement using distilled water as a reference using a colorimeter (JIS Z8722 standard (field of view: 10 degrees, light source: D65, measurement conditions: St, f, W10)).
[0128] Color difference (ΔE* ab ) is calculated from the chromaticity values of the titanium oxide particle dispersion of the evaluated object and the titanium oxide particle dispersion of the comparative sample obtained by the above method using the above calculation formula described in JIS Z8781-4.
[0129] (3) Acetaldehyde gas decomposition performance test of titanium oxide particles
[0130] On one side of a PET film of A4 size (210 mm × 297 mm), each titanium oxide particle dispersion prepared in the embodiment or comparative example is spread over by a #7 wire bar coater in such a manner that the dry mass of the titanium oxide particles reaches about 20 mg, to prepare an evaluation sample, and then dried in an oven set at 80°C for 1 hour to obtain a sample for evaluating the acetaldehyde gas decomposition performance.
[0131] The photocatalytic activity of the titanium oxide particles was evaluated by a decomposition reaction of acetaldehyde gas using the evaluation sample. The evaluation was performed by a batch gas decomposition performance evaluation method.
[0132] Specifically, after placing the evaluation sample in a stainless steel cuvette with a quartz glass window of a volume of 5L, the cuvette is filled with acetaldehyde gas of an initial concentration (20ppm) adjusted to 50% humidity, and irradiated with light from a light source set on the top of the cuvette. When the acetaldehyde gas is decomposed by the photocatalytic action of titanium oxide, the acetaldehyde gas concentration in the cuvette decreases. Here, by measuring the concentration change, the intensity of the photocatalytic activity can be confirmed. Regarding the acetaldehyde concentration, a photoacoustic multi-gas monitor (trade name "INNOVA 1412", manufactured by LumaSense) was used to measure the acetaldehyde gas concentration from the start of light irradiation to 10 hours later, and the decrease in the acetaldehyde gas concentration (the concentration difference between the initial value and the measured value after 10 hours) was confirmed. It shows that the greater the decrease in the acetaldehyde gas concentration, the higher its photocatalytic activity; the smaller the decrease in the acetaldehyde gas concentration, the lower its photocatalytic activity.
[0133] As the test light source, a UV fluorescent lamp (product model "FL10 BLB", Toshiba Lighting & Technology Corporation) was used at an irradiance of 0.5 mW / cm 2 The ultraviolet rays were irradiated under the conditions of . At this time, the initial acetaldehyde concentration in the cuvette was 20 ppm.
[0134] (4) Identification of the Crystal Phase of Titanium Oxide Particles
[0135] The obtained titanium oxide particle dispersion was dried at 105° C. for 3 hours and the titanium oxide particle powder was recovered and subjected to powder X-ray diffraction measurement (trade name “desktop X-ray diffractometer D2 PHASER”, Bruker AXS Ltd.) to identify the crystal phase of the titanium oxide particles.
[0136] (5) Preparation of titanium oxide particle dispersion
[0137] [Preparation Example 1-1]
[0138] <Preparation of a dispersion of titanium oxide particles containing tin as a solid solution>
[0139] Tin (IV) chloride was added / dissolved in a 36 mass % titanium (IV) chloride aqueous solution in a Ti / Sn (molar ratio) of 20, and after diluting it 10 times with pure water, 10 mass % ammonia water was slowly added for neutralization and hydrolysis, thereby obtaining a precipitate of titanium hydroxide containing tin. The pH at this time was 8. The obtained precipitate was repeatedly added with pure water and decanted for deionization. 2 O 2 35 mass % of hydrogen peroxide was added to the deionized tin-containing titanium hydroxide precipitate so that / (Ti+Sn) (molar ratio) was 10, and then stirred at 60° C. for 2 hours to allow sufficient reaction, thereby obtaining an orange transparent tin-containing peroxotitanic acid solution (1a).
[0140] 400 mL of a peroxotitanic acid solution (1a) containing tin was added to an autoclave having a volume of 500 mL, and the solution was subjected to a hydrothermal treatment at 150° C. for 90 minutes. Then, pure water was added to adjust the concentration, thereby obtaining a dispersion of titanium oxide particles (1A) in which tin was dissolved (solid content concentration 1.5% by mass). When the titanium oxide particles (1A) were subjected to powder X-ray diffraction measurement, the peak observed was only that of rutile titanium oxide, indicating that tin was dissolved in the titanium oxide.
[0141] [Preparation Example 1-2]
[0142] <Preparation of a dispersion of titanium oxide particles containing tin as a solid solution>
[0143] A dispersion of titanium oxide particles (1B) in which tin was solid-dissolved was obtained in the same manner as in Preparation Example 1-1, except that tin (IV) chloride was added in a Ti / Sn (molar ratio) of 10 and the hydrothermal treatment time was set to 120 minutes. When the titanium oxide particles (1B) were subjected to powder X-ray diffraction measurement, the peak observed was only the peak of rutile titanium oxide, indicating that tin was solid-dissolved in the titanium oxide.
[0144] [Preparation Example 1-3]
[0145] <Preparation of a dispersion of titanium oxide particles containing tin and manganese as solid solutions>
[0146] A dispersion of titanium oxide particles (1C) in which tin and manganese were dissolved was obtained in the same manner as in Preparation Example 1-1, except that manganese (II) chloride was further added to a 36% by mass titanium (IV) chloride aqueous solution in a Ti / Mn (molar ratio) of 100. When the titanium oxide particles (1C) were subjected to powder X-ray diffraction measurement, the peaks observed were only those of rutile titanium oxide, indicating that tin and manganese were dissolved in the titanium oxide.
[0147] [Preparation Example 1-4]
[0148] <Preparation of Titanium Oxide Particle Dispersion>
[0149] A dispersion of titanium oxide particles (1D) (solid content concentration 1.5 mass %) was obtained in the same manner as in Preparation Example 1-1, except that tin (IV) chloride was not added to the 36 mass % titanium (IV) chloride aqueous solution and the hydrothermal treatment was performed at 130° C. for 90 minutes. When the titanium oxide particles (1D) were subjected to powder X-ray diffraction measurement, the peak observed was a peak of anatase-type titanium oxide.
[0150] The raw material ratio, hydrothermal treatment conditions, and dispersed particle size (D 50 , D 90 ) are summarized in Table 1. The dispersed particle size was measured by a dynamic light scattering method using laser (ELSZ-2000ZS (Otsuka Electronics Co., Ltd., Japan).
[0151] Table 1
[0152]
[0153] (6) Preparation of a solution containing a manganese component and / or a cobalt component
[0154] [Preparation Example 2-1]
[0155] <Preparation of Manganese Chloride Aqueous Solution>
[0156] Manganese (II) chloride tetrahydrate was dissolved in pure water to give a manganese chloride aqueous solution (2A).
[0157] [Preparation Example 2-2]
[0158] <Preparation of Cobalt Chloride Aqueous Solution>
[0159] Cobalt chloride (II) hexahydrate was dissolved in pure water to give a cobalt chloride aqueous solution (2B).
[0160] [Preparation Example 2-3]
[0161] <Preparation of an aqueous solution of manganese chloride and active silicic acid>
[0162] SiO 2 JIS No. 3 sodium silicate was dissolved in pure water so as to be 2% by mass. A strong acidic cation exchange resin (Amberjet 1024H (manufactured by Organo Co Ltd)) was added while stirring the sodium silicate aqueous solution until the pH reached 3.9, and the ion exchange resin was filtered to obtain an active silicic acid aqueous solution. Furthermore, manganese (II) chloride tetrahydrate was dissolved in the active silicic acid aqueous solution so as to be 0.23% by mass, thereby obtaining an aqueous solution (2C) of manganese chloride and active silicic acid.
[0163] [Preparation Example 2-4]
[0164] <Preparation of an aqueous solution of manganese chloride and active silicic acid>
[0165] SiO 2 JIS No. 3 sodium silicate was dissolved in pure water in a manner to convert to 0.5 mass %. A strong acidic cation exchange resin (Amberjet 1024H (manufactured by Organo Co Ltd)) was added while stirring the sodium silicate aqueous solution until the pH reached 4.0, and the ion exchange resin was filtered to obtain an active silicic acid aqueous solution. Furthermore, manganese (II) chloride tetrahydrate was dissolved in the active silicic acid aqueous solution in a manner to obtain 0.23 mass %, thereby obtaining an aqueous solution of manganese chloride and active silicic acid (2D).
[0166] [Preparation Example 2-5]
[0167] <Preparation of Active Silicic Acid Aqueous Solution>
[0168] SiO 2 Sodium silicate of JIS No. 3 was dissolved in pure water so as to be converted to 2% by mass. A strongly acidic cation exchange resin (Amberjet 1024H (manufactured by Organo Co. Ltd.)) was added while stirring the sodium silicate aqueous solution until the pH reached 3.9, and then the ion exchange resin was filtered to obtain an active silicic acid aqueous solution (2E).
[0169] (7) Preparation of titanium oxide particle dispersion
[0170] [Example 1]
[0171] The titanium oxide particle dispersion (1A) and the manganese chloride aqueous solution (2A) were mixed so that Ti / Mn (molar ratio) was 4:34, thereby obtaining a titanium oxide particle dispersion (E-1).
[0172] [Example 2]
[0173] The titanium oxide particle dispersion (1A) and the manganese chloride aqueous solution (2A) were mixed so that the Ti / Mn (molar ratio) was 2174, thereby obtaining a titanium oxide particle dispersion (E-2).
[0174] [Example 3]
[0175] The titanium oxide particle dispersion (1B) and the cobalt chloride aqueous solution (2B) were mixed so that the Ti / Co (molar ratio) was 187, thereby obtaining a titanium oxide particle dispersion (E-3).
[0176] [Example 4]
[0177] Titanium oxide particle dispersion (E-4) was obtained by mixing titanium oxide particles (1A), manganese chloride, and an aqueous solution of active silicic acid (2C) so that Ti / Mn (molar ratio) was 92 and Ti / Si (molar ratio) was 3.
[0178] [Example 5]
[0179] Titanium oxide particle dispersion (E-5) was obtained by mixing titanium oxide particles (1A), manganese chloride, and an aqueous solution of active silicic acid (2C) so that Ti / Mn (molar ratio) was 434 and Ti / Si (molar ratio) was 15.
[0180] [Example 6]
[0181] Titanium oxide particle dispersion (E-6) was obtained by mixing titanium oxide particles (1A), manganese chloride, and an aqueous solution of active silicic acid (2D) so that Ti / Mn (molar ratio) was 48 and Ti / Si (molar ratio) was 7.
[0182] [Comparative Example 1]
[0183] A titanium oxide particle dispersion (C-1) was obtained from only the titanium oxide particles (1A).
[0184] [Comparative Example 2]
[0185] A titanium oxide particle dispersion (C-2) was obtained from only the titanium oxide particles (1C).
[0186] [Comparative Example 3]
[0187] The titanium oxide particles (1D) and the manganese chloride aqueous solution (2A) were mixed so that the Ti / Mn (molar ratio) was 2174, thereby obtaining a titanium oxide particle dispersion (C-3).
[0188] [Comparative Example 4]
[0189] The titanium oxide particles (1A) and the active silicic acid aqueous solution (2E) were mixed so that the Ti / Si (molar ratio) was 3, thereby obtaining a titanium oxide particle dispersion (C-4).
[0190] Table 2 summarizes the molar ratios of the liquid and the metal used in the titanium oxide dispersions prepared in Examples and Comparative Examples.
[0191] Table 2
[0192]
[0193] The dispersed particle size (D 50 , D 90 ), acetaldehyde gas decomposition test results (concentration after 10 hours and the extent of concentration reduction), chromaticity value (L*a*b*), and color difference (ΔE*) with the titanium oxide particle dispersion of the comparative sample ab ) are summarized in Table 3. The dispersed particle size was measured by a dynamic light scattering method using laser (ELSZ-2000ZS (manufactured by Otsuka Electronics Co., Ltd.); the chromaticity value was measured by a spectroscopic colorimeter / turbidity simultaneous measuring instrument TZ7700 (manufactured by Nippon Denshoku Industries Co., Ltd.).
[0194] Table 3
[0195]
[0196] From Comparative Examples 1 and 4, it is understood that titanium oxide containing no manganese and / or cobalt components has high acetaldehyde gas decomposition ability and high photocatalytic activity.
[0197] From Comparative Example 2, it is understood that the photocatalytic activity of titanium oxide in which manganese is solid-solved is suppressed, but the color difference is large.
[0198] From Comparative Example 3 and Example 2, it can be seen that titanium oxide without tin solid solution has high photocatalytic activity even if it contains manganese components.
Claims
1. A titanium oxide particle comprising: 1) tin content, and 2) Manganese content Titanium oxide particles, in, Only the tin component is dissolved in the titanium oxide particles. The content of the manganese component is 5 to 5000 in terms of the molar ratio of titanium to manganese (Ti / Mn). 2 . A member comprising a film of the titanium oxide particles according to claim 1 .
3. A titanium oxide particle dispersion comprising: 1) Titanium oxide particles in which tin is dissolved, and 2) Manganese content A titanium oxide particle dispersion, wherein Only the tin component is solid-solved in the titanium oxide particles, wherein the content of the manganese component is 5 to 5000 in terms of a molar ratio Ti / Mn of titanium to manganese.
4. The titanium oxide particle dispersion according to claim 3, wherein Solid content concentration of 1% by mass Color difference ΔE* between (a) a titanium oxide particle dispersion containing a tin component in a solid solution and having a tin component content of 20 in terms of a molar ratio of titanium to tin Ti / Sn and (b) the titanium oxide particle dispersion according to claim 3 ab Below 30.
5. The titanium oxide particle dispersion according to claim 3 or 4, in, It also contains silicon.
6. The titanium oxide particle dispersion according to claim 3 or 4, in, The content of the tin component dissolved in titanium oxide is 1 to 1000 in terms of a molar ratio Ti / Sn of titanium to tin.
7. The titanium oxide particle dispersion according to claim 3 or 4, in, The content of the manganese component is 10 to 3000 in terms of the molar ratio of titanium to manganese (Ti / Mn).
8. The method for producing a titanium oxide particle dispersion according to claims 3 to 7, characterized in that: The method comprises the following steps (1) to (4): (1) a step of preparing a peroxotitanic acid solution containing a tin component from a raw material titanium compound, a tin compound, an alkaline substance, hydrogen peroxide and an aqueous dispersion medium; (2) a step of heating the peroxotitanic acid solution containing tin component produced in the above step (1) at 80 to 250° C. under pressure control to obtain a titanium oxide particle dispersion containing tin component; (3) a step of obtaining an aqueous solution or aqueous dispersion of a manganese component from a raw material manganese compound and an aqueous dispersion medium; (4) A step of mixing the titanium oxide particle dispersion containing the tin component produced in the step (2) and the aqueous solution or aqueous dispersion of the manganese component produced in the step (3).
Citation Information
Patent Citations
Titanium oxide fine article
JP1988225532A
Rutile type titanium dioxide fine grain and production method thereof
JP2003327430A
Rutile type titanium dioxide fine grain and production method thereof
JP2003327431A
Polymer-bound ultraviolet absorber, ultraviolet absorber composition, ultraviolet screening composition, method for producing the same and processed article using the same
JP2005120137A
Organic solvent dispersion of titanium oxide solid-solution particles, making method, and coating composition
CN105017841A